آليات الرقابة المالية في المؤسسات العمومية ذات الطابع الإداري في ظل المستجدات المالية - بلخيري، محمد سعد الدين; فنيري، يمينة (University of Eloued جامعة الوادي, 2025)
هدفت هذه الدراسة إلى إبراز آليات الرقابة المالية في المؤسسات العمومية ذات الطابع الإداري في ظل المستجدات المالية في الجزائر، وحصرا بعد القانون العضوي 18-15، المتعلق بالقوانين المالية والإصلاح الميزانياتي، وللإجابة على إشكالية الدراسة؛ تم الاعتماد على أسلوب دراسة الحالة ضمن المنهج الوصفي مع اختيار حالة المؤسسة العمومية للصحة الجوارية -شلغوم العيد- ميلة، خلال 2018 – 2024. توصلت النتائج إلى أن القانون العضوي 18-15، يتضمن مجموعة من الأحكام التي ساهمت في تحسين وضعية الميزانية العمومية في الجزائر، وذلك في ضوء التوجهات الحديثة التي أرسى دعائمها واعتماده لأساليب تسيير مبتكرة This research examines financial control mechanisms in Algerian public institutions under Organic Law 18-15. Using a case study of Chelghoum El Aid Health Institution (2018-2024), the study reveals the law's effectiveness in modernizing financial oversight. Key findings show enhanced budget management through results-based approaches, increased transparency, and improved accountability. The law successfully shifted control systems from traditional input monitoring to performance-oriented frameworks, demonstrating significant improvements in public spending efficiency.
Mechanisms of Budgetary Control in Public Administrative Institutions in Light of Financial Developments A Case Study of the Local Public Health Establishment of Chelghoum Laïd – Mila
مقال
Keywords: الرقابة المالية; القانون العضوي 18-15; المؤسسات العمومية; المراقب الميزانياتي; Financial Control; Organic Law18-15; Public Institutions; CB